Nutrient recycling through liquid digestate use in ornamental crop fertilizations - Beily, María Eugenia; Rubio, Esteban Julian; Karlanian, Monica; Vila Moret, Marcos; Riera, Nicolas Iván (INTA y Sbera, 2026)
Poster